Analysis of Overmacht Credit Agreements During Pandemic (Case Study of Loss Claims Rejections By Judges) - Rully Syahrul Mucharom; Toto Tohir Suriaatmadja; Dey Ravena; M. Faiz Mufidi (Faculty of Law, Universitas Pekalongan, 2022)
The purpose of this research is to identify and analyze Covid-19 as a form of comparative advantage and the consequences of the advantage method in loan agreements and loan termination policies due to the Covid-19 pandemic. The research method is norm-law. It is a legal research method that examines and studies the provisions of legislation as a basis for subsequent analysis of the issues discussed. The research uses primary and secondary legal material for analysis through the study of relevant documents and literature. The analysis is a qualitative analysis that addresses the question in question. According to the research, Covid-19 is an unnatural disaster and thus can be classified as a measure of superiority. As a priority relationship, the laws governing the spread of Covid-19 result in a priority relationship with the loan agreement, which means that the debtor must continue to meet his obligations to the debtor even after Covid-19 is over. When it was implemented following POJK 11/2020, the debtor obtained credit relief through restructuring in the form of interest rate cuts, extension of maturity, reduction of funds owed, and interest reduction in arrears according to the restructuring table issued by the bank. After verification and analysis by the bank, the affected debtor Covid- 19